Three-Dimensional, Real-Time, and Intelligent Data Acquisition of Large Deformation in Deep Tunnels - Yue-Mao Zhao; Yong Han; Yong-Yuan Kou; Lin Li; Jiu-Hua Du (Advances in Civil Engineering)
Potential disasters of large deformation pose serious threats to deep underground projects such as tunnels and mines. Engineering with large deformation is typically characterized by high stress, complex engineering geology, strong disturbance, and squeezing deformation, posing a great challenge to the design of an effective and accurate monitoring system. To address this problem, it is necessary to grasp the three-dimensional features of deformation and establish integrated monitoring of a support system. Monitoring equipment should be selected to obtain joint, stress, deformation, cracking process, and other information, and this information can be fed back to the warning and control module. The scheme of the monitoring system presented here was successfully applied to a deep metal mine. This intelligent monitoring system ensures safety during the construction and operation of the tunnel under complex surrounding rock conditions, allows the use of field monitoring data to guide construction and design, and provides a reference for future construction and project monitoring.